Preparation method of hot air aging resistant and high and low temperature medium resistant fluorinated polyphosphazene and interpenetrating network elastomer thereof
By introducing high fluorinated side groups and low-temperature resistant rubber raw rubber into fluorinated polyphosphazene materials, the interpenetrating network structure is constructed, and the problem of poor sealing performance of existing fluorinated polyphosphazene materials under extreme conditions is solved, and excellent high-temperature resistance and heat-air aging resistance are achieved.
Patent Information
- Application Number
- CN202510012075.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
The existing fluorinated polyphosphazene materials have poor sealing performance under extreme conditions, especially in high and low temperature media environments, which are prone to seal failure.
By introducing high fluorinated side groups such as perfluorooctanoxy to the main chain structure of traditional fluorinated polyphosphazene, and adding a second low-temperature resistant rubber raw rubber to it, an interpenetrating network structure is constructed, and fluorinated polyphosphazene or its interpenetrating network elastomer is obtained through co-vulcanization treatment.
It improves the high and low temperature media resistance and heat-air aging resistance of fluorinated polyphosphazene materials, and meets the sealing needs under extreme conditions.
Smart Images

Figure BDA0005228758510000091 
Figure HDA0005228758530000011 
Figure HDA0005228758530000012
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a fluorinated polyphosphazene and an interpenetrating network elastomer thereof that is resistant to heat air aging and high and low temperature media, and the specific purpose is to improve the heat air aging resistance and high and low temperature media resistance performance of the fluorinated polyphosphazene and the interpenetrating network elastomer thereof to meet the sealing requirements under extreme conditions. Background Art
[0002] Rubber products are increasingly widely used in the fields of automobiles, aerospace, oil extraction, etc. With the in-depth development of these fields, the demand for rubber continues to increase, and the requirements for rubber performance are becoming more and more stringent, especially in the fields of aerospace, polar exploration, etc., which put forward higher requirements on the extreme cold resistance, hot air aging resistance, and high and low temperature medium resistance of rubber products.
[0003] The oil resistance of rubber products depends on the chemical properties of the rubber matrix and oils. Oil chemicals can penetrate into rubber products and swell them, causing them to deform and become unstable, and the mechanical strength and other mechanical properties to decrease. According to the principle of similar compatibility, rubber products containing polar groups in the molecules are stable to non-polar oils; rubber containing non-polar groups in the molecules are stable to polar oils. The cold resistance of rubber products refers to the ability of rubber to maintain its elasticity and be very stable at a certain low temperature, which mainly depends on the two basic processes of polymers: glass transition and crystallization. The glass transition temperature (Tg) is the transition temperature from the movement to freezing of the molecular chain segments of the rubber. The movement of the chain segments is achieved by the rotation of the single bonds in the main chain, so the flexibility of the rubber molecular chain determines the cold resistance of the rubber. Factors that weaken the flexibility of the molecular chain or increase the intermolecular force, such as the introduction of polar side groups, bulky side groups, cross-linking, and crystallization, will increase Tg; conversely, factors that increase the flexibility of the molecular chain, such as adding softeners or introducing flexible groups, will reduce Tg. The strength and mechanical properties of rubber products are mainly related to the structure of rubber molecules, reinforcement system, and vulcanization system. Based on this principle, previous studies have designed and prepared a series of low-temperature and medium-resistant rubber materials. Due to its strong structural designability, polyphosphazene can flexibly introduce polar / non-polar and highly flexible groups into its structure, giving it extreme cold resistance and certain high and low temperature medium resistance. However, existing studies have shown that the currently designed fluorinated polyphosphazenes, such as trifluoroethoxy / octafluoropentyloxy polyphosphazenes, have poor high and low temperature medium resistance due to their relatively high compression permanent deformation, which can lead to sealing failure under such harsh conditions.
[0004] Based on this, the present invention intends to first prepare a new type of fluorinated polyphosphazene rubber raw rubber by introducing a certain amount of high-fluorinated side groups such as perfluorooctoxy groups into the main chain structure of traditional fluorinated polyphosphazene. Then, a certain amount of a second low-temperature resistant rubber raw rubber is introduced into the new fluorinated polyphosphazene raw rubber. Finally, the mixed raw rubber is co-vulcanized under certain conditions to obtain a fluorinated polyphosphazene or an interpenetrating network elastomer thereof. By adjusting the fluorinated side group structure in the fluorinated polyphosphazene and the interpenetrating network structure in the polymer material, its compression permanent deformation is increased, thereby indirectly improving the high and low temperature medium resistance of the rubber material, while maintaining excellent heat air aging resistance, so as to meet the application requirements of high-performance sealing materials. Summary of the invention
[0005] The invention discloses a preparation method of a fluorinated polyphosphazene which is resistant to heat air aging and high and low temperature media and an interpenetrating network elastomer thereof.
[0006] The technical problem to be solved by the present invention relates to the preparation of heat-air aging-resistant, high-low temperature medium-resistant fluorinated polyphosphazene and its interpenetrating network elastomer for sealing applications.
[0007] The preparation method of the fluorinated polyphosphazene and its interpenetrating network elastomer resistant to heat air aging and high and low temperature media according to the present invention mainly comprises the following steps:
[0008] Step 1: prepare polydichlorophosphazene according to bulk polymerization or other methods, and dissolve it in a suitable solvent such as xylene or tetrahydrofuran to obtain a polydichlorophosphazene solution for standby use, drop the corresponding sodium salt of fluoroalcohol or / and sodium salt of fluoroalcohol into the polydichlorophosphazene solution, and make the sodium salt undergo full substitution reaction at a suitable temperature for 24 to 72 hours, then precipitate the polymer with a precipitant such as petroleum ether, n-hexane, n-heptane, and dry to obtain a linear fluorinated polyphosphazene raw rubber;
[0009] Step 2: dissolving 1 to 100 parts by weight of the linear fluorinated polyphosphazene in an appropriate solvent such as tetrahydrofuran or N, N-dimethylformamide to obtain a linear fluorinated polyphosphazene glue solution of a certain mass concentration, and then adding 0 to 99 parts of a second low-temperature resistant rubber raw rubber or its monomer to the glue solution. If the monomer is added, continue to add an appropriate amount of initiator, and react at an appropriate temperature until the polymerization is completed to obtain a mixed polymer glue solution;
[0010] Step 3: Add a certain amount of reinforcing agent, accelerator, vulcanizing agent and other fillers to the mixed polymer glue, and stir well to obtain a raw rubber mixture. After the solvent evaporates, the raw rubber mixture is thinly passed on an open mill for multiple times, such as 6 times, and then a sheet is produced, and the raw rubber sheet is co-vulcanized at a certain vulcanization temperature for 0.5 to 4 hours to finally obtain a fluorinated polyphosphazene or an interpenetrating network elastomer thereof.
[0011] Preferably, the fluorinated polyphosphazene rubber matrix, the side group substituent group of which adopts sodium fluoroalcohol salt or / and sodium fluoroalcohol salt is one or more of sodium m-trifluoromethylphenol, sodium perfluorodecyl alcohol, sodium perfluorooctanol, sodium perfluorohexyl ethoxide, sodium 2-allyl hexafluoroisopropanol, sodium trifluoroethoxide, sodium tetrafluoropropanol, sodium hexafluorobutanol, sodium hexafluoroisopropanol, sodium heptafluorobutanol, sodium heptafluoroisopropanol, sodium octafluoropentanol, sodium perfluoro tert-butanol or sodium dodecafluoroheptanol; wherein it preferably contains perfluorodecyloxy or perfluorooctyloxy or perfluorohexylethoxy side groups, and the proportion of perfluorodecyloxy or perfluorooctyloxy or perfluorohexylethoxy side groups is greater than or equal to 50%.
[0012] Preferably, the fluorinated polyphosphazene raw rubber is 50-100 parts, and the second low-temperature resistant rubber raw rubber is 0-50 parts; preferably, the total amount of the two is 100 parts.
[0013] Preferably, the second low-temperature resistant rubber raw rubber is one or more of silicone rubber, fluororubber, fluoroether rubber, fluorosilicone rubber, nitrile rubber, hydrogenated nitrile rubber, polyurethane rubber, ethylene-propylene rubber, styrene-butadiene rubber, natural rubber, polybutadiene rubber, isoprene rubber, acrylate rubber and the like; wherein the second low-temperature resistant rubber preferably contains hydrogenated nitrile rubber, and the proportion of hydrogenated nitrile rubber is greater than or equal to 70%.
[0014] Preferably, the mass concentration of the mixed solution of fluorinated polyphosphazene and the second low-temperature resistant rubber raw rubber is 10%-15%, which is beneficial for uniformly dispersing the filler and also helps the volatilization of the solvent.
[0015] Preferably, the reinforcing agent is a carbon black / white carbon black mixed mass ratio of 3:1, the particle size of the carbon black is 60-100 nanometers, the particle size of the white carbon black is 50-100 nanometers, and the added mass fraction is 5 to 15 parts;
[0016] Preferably, the accelerator is one or a combination of zinc oxide, magnesium oxide, zinc stearate and magnesium stearate, and the added mass fraction is 6 to 10 parts.
[0017] Preferably, the vulcanizing agent is a peroxide vulcanizing agent or a compound of a peroxide vulcanizing agent and sulfur. The compounding mass ratio is preferably 1:1. The peroxide includes at least one of the following: diisopropyl benzene peroxide, di(tert-butyl peroxide isopropyl) benzene, dibenzoyl peroxide, di(2,4-dichlorobenzoyl peroxide), 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(peroxybenzoyl) hexane, 2,5-dimethyl-2,5-bis(tert-butyl peroxy) hexane, di-tert-butyl peroxide, 1,1-bis(tert-butyl peroxy) cyclohexane, etc., and the added mass fraction is 0.1 to 5 parts.
[0018] Preferably, the vulcanization process is vulcanization at 60-90° C. for 0.5 hour and vulcanization at 120-160° C. for 2 hours.
[0019] In summary, compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:
[0020] 1. In the fluorinated polyphosphazene side groups of the present invention, the proportion of perfluorodecyloxy, perfluorooctyloxy or perfluorohexylethoxy is greater than 50%. The role of the long carbon chain alkyl group is to provide a stronger chain rotation ability and improve the flexibility of the polymer, thereby further reducing the glass transition temperature and meeting the requirements of extremely low temperature use; on the other hand, the selection of high fluorine content side groups helps to improve the medium resistance.
[0021] 2. By constructing a fluorinated polyphosphazene interpenetrating network, the excellent properties of each polymer in the interpenetrating network structure, such as resistance to hot air aging and low compression permanent deformation, are absorbed, and the high anti-swelling property of the interpenetrating network is used to improve its resistance to high and low temperature solvent media.
[0022] 3. The polymer and its interpenetrating network elastomer material are aged in hot air at 150°C for 72 hours, and the change rate of tensile strength is less than 1%, and the change of elongation at break is less than 10%; the glass transition temperature is adjustable within the temperature range of -50°C to -80°C, and after immersion treatment in various types of high and low temperature media at -60°C to 150°C, the change rate of mechanical properties of fluorinated polyphosphazene and its interpenetrating network elastomer is less than 5%, showing excellent high and low temperature medium tolerance.
[0023] It can therefore be used as a sealing material under various harsh conditions.
[0024] The present invention will be described in detail below with reference to the accompanying drawings and embodiments to make the purpose and effects of the present invention more obvious. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the synthesis equation of the fluorinated polyphosphazene described in Example 1, which only represents the synthesis of a fluorinated polyphosphazene containing perfluorooctyloxy group, and the synthesis steps of polyphosphazenes with other side group types and different ratios are consistent with the synthesis steps, only the side group type and the side group ratio are changed.
[0026] Figure 2 This is the glass transition temperature curve of the fluorinated polyphosphazene rubber in Example 1.
[0027] Figure 3 This is a photo of the appearance of the fluorinated polyphosphazene sealing ring of Example 2 and a diagram of the sealing test experimental device. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the following embodiments.
[0029] Embodiment 1:
[0030] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.188mol perfluorodecyl alcohol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -64.8°C.
[0031] Step 2: Take 50 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 5% glue solution, and then add 50 parts of hydrogenated nitrile rubber to the glue solution to obtain a mixed polymer glue solution.
[0032] Step 3: Add 5 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 10 parts by mass of zinc oxide and 0.5 parts by mass of diisopropylbenzene peroxide to the mixed polymer rubber solution and stir them thoroughly to obtain a raw rubber mixture. After the solvent is evaporated, the raw rubber mixture is passed through an open mixing mill for 6 times and then sheeted. Subsequently, it is co-vulcanized at 90°C for 0.5 hour and at 160°C for 2 hours to obtain a fluorinated poly-hydrogenated nitrile interpenetrating network elastomer sealing material, which is then made into strips and sealing ring samples for testing.
[0033] After aging in hot air at 150℃ for 72 hours, the change rate of tensile strength is 0.9%, and the change rate of elongation at break is 9.5%; after aging at 150℃ for 72 hours, the permanent deformation is 30%. After being placed in 15# aviation hydraulic oil at -56℃ and 150℃ for 24 hours, the change rate of tensile strength is less than 4.5%, and the change rate of elongation at break is less than -5%. In the liquid sealing test, 15# aviation hydraulic oil is maintained at 120℃ and 1MPa for 1 hour without leakage, and the pressure holding rate is 99.5%.
[0034] Embodiment 2:
[0035] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.188mol perfluorodecyl alcohol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -66°C.
[0036] Step 2: Take 100 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 10% glue solution by mass concentration, and obtain a fluorinated polyphosphazene polymer glue solution.
[0037] Step 3: Add 10 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 8 parts by mass of zinc oxide, and 0.6 parts by mass of diisopropylbenzene peroxide to the polymer rubber solution and stir them thoroughly to obtain a raw rubber mixture. After the solvent is evaporated, the raw rubber mixture is passed through an open mixing mill for 6 times to produce a sheet, which is then vulcanized at 90°C for 0.5 hour and at 160°C for 2 hours to obtain a fluorinated polyphosphazene elastomer sealing material, which is then made into strips and sealing ring samples for testing.
[0038] After aging in hot air at 150℃ for 72 hours, the change rate of tensile strength is 0.96%, and the change rate of elongation at break is 10%; after aging at 150℃ for 72 hours, the permanent deformation is 40%. After being placed in 15# aviation hydraulic oil at -56℃ and 150℃ for 24 hours, the change rate of tensile strength is less than 4.9%, and the change rate of elongation at break is less than -4.7%. In the liquid sealing test, 15# aviation hydraulic oil is maintained at 120℃ and 0.8MPa for 1 hour without leakage, and the pressure holding rate is 99.5%.
[0039] Embodiment 3:
[0040] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.145mol perfluorooctanol sodium salt, 0.114mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 50% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -68°C.
[0041] Step 2: Take 100 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 10% glue solution by mass concentration, and obtain a fluorinated polyphosphazene polymer glue solution.
[0042] Step 3: Add 9 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 6 parts by mass of zinc oxide, and 0.5 parts by mass of diisopropylbenzene peroxide to the polymer rubber solution and stir them thoroughly to obtain a raw rubber mixture. After the solvent is evaporated, the raw rubber mixture is passed through an open mixing mill for 6 times to produce a sheet, which is then vulcanized at 80°C for 0.5 hour and at 140°C for 2 hours to obtain a fluorinated polyphosphazene elastomer sealing material, which is then made into strips and sealing ring samples for testing.
[0043] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 0.92%, and the change rate of elongation at break was 8.7%. After aging at 150°C for 72 hours, the permanent deformation of compression was 44%. After being placed in RIPP55 aviation oil at -56°C and 150°C for 24 hours, the change rate of tensile strength was less than 4.9%, and the change rate of elongation at break was less than -4.7%. In the liquid sealing test, RIPP55 aviation oil was kept at 120°C and 0.8MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0044] Embodiment 4:
[0045] Step 1: According to the bulk polymerization method, 10g of linear polydichlorophosphazene is prepared by precipitation in petroleum ether, the linear polydichlorophosphazene is dissolved in xylene and then dripped into a mixed sodium salt consisting of 0.188mol perfluorohexylethanol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, reacted at room temperature for 24 hours, and the polymer solution was precipitated with 2000ml water and 2000ml n-hexane to prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -67.5°C.
[0046] Step 2: Take 100 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 10% glue solution by mass concentration, and obtain a fluorinated polyphosphazene polymer glue solution.
[0047] Step 3: Add 11 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 6 parts by mass of zinc oxide and 1 part by mass of diisopropylbenzene peroxide to the polymer rubber solution respectively and stir them thoroughly to obtain a raw rubber mixture. After the solvent is evaporated, the raw rubber mixture is passed through an open mixing mill for 6 times and then sheeted. Subsequently, it is vulcanized at 90°C for 0.5 hour and at 150°C for 2 hours to obtain a fluorinated polyphosphazene elastomer sealing material, which is then made into strips and sealing ring samples for testing.
[0048] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 0.97%, and the change rate of elongation at break was 10%. After aging at 150°C for 72 hours, the permanent deformation of compression was 43%. After being placed in RIPP55 aviation oil at -56°C and 150°C for 24 hours, the change rate of tensile strength was less than 3.7%, and the change rate of elongation at break was less than -4.1%. In the liquid sealing test, RIPP55 aviation oil was kept at 120°C and 0.8MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0049] Embodiment 5:
[0050] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.188mol perfluorodecyl alcohol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -66°C.
[0051] Step 2: Take 50 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 5% glue solution, and then add 50 parts of hydrogenated nitrile / fluorosilicone rubber raw rubber (hydrogenated nitrile accounts for 70%) to the glue solution to obtain a mixed polymer glue solution.
[0052] Step 3: Add 5 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 10 parts by mass of zinc oxide, and 0.7 parts by mass of diisopropylbenzene peroxide-sulfur (the mass ratio of diisopropylbenzene peroxide-sulfur is 1:1) into the mixed polymer rubber solution and stir well to obtain a raw rubber mixture. After the solvent evaporates, pass the raw rubber mixture on an open mixing mill for 6 times and then produce a sheet. Subsequently, vulcanize it at 90°C for 0.5 hour and at 160°C for 2 hours to obtain a fluorinated poly-fluorosilicone rubber interpenetrating network elastomer sealing material, and make it into splines and sealing ring samples for testing.
[0053] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 0.3%, and the change rate of elongation at break was -1.5%. After aging at 150°C for 72 hours, the permanent deformation of compression was 16%. After being placed in DOD-PRF-85734A aviation oil at 150°C for 24 hours, the change rate of tensile strength was less than 4.5%, and the change rate of elongation at break was less than -5%. In the liquid sealing test, DOD-PRF-85734A aviation oil was maintained at 120°C and 1MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0054] Embodiment 6:
[0055] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.145mol perfluorodecyl alcohol sodium salt, 0.14mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 50% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -66°C.
[0056] Step 2: Take 60 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 5% glue solution, and then add 40 parts of hydrogenated nitrile / fluoroether rubber raw rubber (hydrogenated nitrile accounts for 70%) to the glue solution to obtain a mixed polymer glue solution.
[0057] Step 3: Add 5.5 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 7 parts by mass of zinc oxide, and 0.6 parts by mass of diisopropylbenzene peroxide-sulfur (the mass ratio of diisopropylbenzene peroxide-sulfur is 1:1) to the mixed polymer rubber solution and stir well to obtain a raw rubber mixture. After the solvent evaporates, pass the raw rubber mixture on an open mixing mill for 6 times and then produce a sheet. Subsequently, vulcanize it at 90°C for 0.5 hour and at 160°C for 2 hours to obtain a fluorinated poly-fluorosilicone rubber interpenetrating network elastomer sealing material, and make it into splines and sealing ring samples for testing.
[0058] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 0.5%, and the change rate of elongation at break was -1.9%. After aging at 150°C for 72 hours, the permanent deformation was 25%. After being placed in DOD-PRF-85734A aviation oil at 150°C for 24 hours, the change rate of tensile strength was below 4.9%, and the change rate of elongation at break was below -4.7%. In the liquid sealing test, DOD-PRF-85734A aviation oil was maintained at 120°C and 1MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0059] Embodiment 7:
[0060] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.188mol perfluorodecyl alcohol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -66°C.
[0061] Step 2: Take 50 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 5% glue solution by mass concentration, and then add 50 parts of fluoroether rubber / hydrogenated nitrile rubber raw rubber to the glue solution, wherein hydrogenated nitrile accounts for 70% of the fluoroether rubber / hydrogenated nitrile rubber raw rubber, to obtain a mixed polymer glue solution.
[0062] Step 3: Add 6 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 10 parts by mass of zinc oxide, and 0.7 parts by mass of diisopropylbenzene peroxide-sulfur (the mass ratio of diisopropylbenzene peroxide-sulfur is 1:1) into the mixed polymer rubber solution and stir well to obtain a raw rubber mixture. After the solvent evaporates, pass the raw rubber mixture on an open mixing mill for 6 times and then produce a sheet. Subsequently, vulcanize it at 90°C for 0.5 hour and at 160°C for 2 hours to obtain a fluorinated poly-fluorosilicone rubber interpenetrating network elastomer sealing material, and make it into splines and sealing ring samples for testing.
[0063] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 1%, and the change rate of elongation at break was 1.3%; after aging at 150°C for 72 hours, the permanent deformation of compression was 19%. After being placed in DOD-PRF-85734A aviation oil at 150°C for 24 hours, the change rate of tensile strength was less than 3.7%, and the change rate of elongation at break was less than -4%. In the liquid sealing test, DOD-PRF-85734A aviation oil was maintained at 120°C and 1MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0064] Embodiment 8:
[0065] Step 1: Prepare 10g of linear polydichlorophosphazene by precipitation in petroleum ether according to the bulk polymerization method, dissolve the linear polydichlorophosphazene in xylene and then drop into a mixed sodium salt consisting of 0.188mol perfluorodecyl alcohol sodium salt, 0.071mol trifluoroethanol sodium salt and 0.03mol octafluoropentanol sodium salt, react at room temperature for 24 hours, precipitate the polymer solution with 2000ml water and 2000ml n-hexane, and prepare a fully substituted fluorinated polyphosphazene with perfluorodecyloxy group accounting for 65% of the molar amount of the side group. The obtained product is vacuum dried in an oven at 50°C to constant weight for standby use, and the product glass transition temperature is -66°C.
[0066] Step 2: Take 50 parts by weight of the fluorinated polyphosphazene rubber in step 1, dissolve it in tetrahydrofuran to prepare a 5% glue solution, and then add 50 parts of isoprene rubber raw rubber / hydrogenated nitrile rubber raw rubber to the glue solution, wherein hydrogenated nitrile accounts for 76% of the isoprene rubber / hydrogenated nitrile rubber raw rubber, to obtain a mixed polymer glue solution.
[0067] Step 3: Add 5 parts by mass of carbon black / white carbon black (the ratio of carbon black / white carbon black is 3:1), 10 parts by mass of zinc oxide, and 0.7 parts by mass of dicumyl peroxide-sulfur (the mass ratio of dicumyl peroxide-sulfur is 1:1) to the mixed polymer rubber solution and stir well to obtain a raw rubber mixture. After the solvent evaporates, pass the raw rubber mixture on an open mixing mill for 6 times and then produce a sheet. Subsequently, vulcanize it at 90°C for 0.5 hour and at 160°C for 3 hours to obtain a fluorinated poly-fluorosilicone rubber interpenetrating network elastomer sealing material, and make it into splines and sealing ring samples for testing.
[0068] After aging in hot air at 150°C for 72 hours, the change rate of tensile strength was 0.25%, and the change rate of elongation at break was 1.3%; after aging at 150°C for 72 hours, the permanent deformation of compression was 17%. After being placed in RIPP555 aviation oil at 150°C for 24 hours, the change rate of tensile strength was less than 4.2%, and the change rate of elongation at break was less than -3%. In the liquid sealing test, RIPP555 aviation oil was maintained at 120°C and 1MPa for 1 hour without leakage, and the pressure holding rate was 99.5%.
[0069] In summary, the fluorinated polyphosphazene or its interpenetrating network elastomeric sealing material of the present invention has the properties shown in the table.
[0070]
[0071] Among them, the change rate of tensile strength = (tensile strength after hot air aging - tensile strength of original sample at room temperature) / tensile strength of original sample at room temperature × 100%; the change rate of elongation at break = (elongation at break after hot air aging - elongation at break of original sample at room temperature) / elongation at break of original sample at room temperature × 100%.
[0072] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.
[0073] For technical personnel, this application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of this application should be included in the protection scope of this application.
Claims
1. A method for preparing a fluorinated polyphosphazene resistant to heat air aging and high and low temperature media and an interpenetrating network elastomer thereof, characterized in that: The following steps are involved: Step 1: Prepare polydichlorophosphazene according to bulk polymerization or other methods, and dissolve it in an appropriate solvent to obtain a polydichlorophosphazene solution for standby use, and drop the corresponding sodium salt of fluoroalcohol or / and sodium salt of fluoroalcohol into the polydichlorophosphazene solution respectively to make the sodium salt fully replace at an appropriate temperature, and then precipitate the polymer with a precipitant, and dry to obtain a linear fluorinated polyphosphazene raw rubber; Step 2: dissolving 1 to 100 parts by mass of the linear fluorinated polyphosphazene in a suitable solvent to obtain a linear fluorinated polyphosphazene glue solution of a certain mass concentration, and then adding 0 to 99 parts of a second low-temperature resistant rubber raw rubber or its monomer to the glue solution, and if the monomer is added, continuing to add an appropriate amount of initiator, and reacting at an appropriate temperature until the polymerization is completed to obtain a mixed polymer glue solution; Step 3: Add a certain amount of filler by mass to the mixed polymer glue, stir it thoroughly to obtain a raw rubber mixture. After the solvent evaporates, the raw rubber mixture is thinly passed on an open mill for multiple times to produce a sheet, and the raw rubber sheet is co-vulcanized at a certain vulcanization temperature to finally obtain a fluorinated polyphosphazene or an interpenetrating network elastomer thereof.
2. The method according to claim 1, characterized in that The fluorinated polyphosphazene rubber matrix has a side-substituted group in which the sodium fluoroalcohol salt is / are one or more of sodium fluoroalcohols selected from the group consisting of sodium m-trifluoromethylphenol, sodium perfluorodecanoate, sodium perfluorooctanol, sodium perfluorohexylethanolate, sodium 2-allylhexafluoroisopropanoate, sodium trifluoroethanolate, sodium tetrafluoropropanoate, sodium hexafluorobutanoate, sodium hexafluoroisopropanoate, sodium heptafluorobutanoate, sodium heptafluoroisopropanoate, sodium octafluoropentanoate, sodium perfluorotert-butanoate or sodium dodecafluoroheptanol.
3. The method according to claim 2, characterized in that The fluorinated polyphosphazene rubber matrix contains perfluorodecyloxy or perfluorooctyloxy or perfluorohexylethoxy side groups, and the perfluorodecyloxy or perfluorooctyloxy or perfluorohexylethoxy side groups account for more than or equal to 50%.
4. The method according to claim 1, characterized in that The fluorinated polyphosphazene raw rubber is 50-100 parts, and the second low-temperature resistant rubber raw rubber is 0-50 parts; preferably, the total amount of the two is 100 parts.
5. The method according to claim 1, characterized in that The second type of low-temperature resistant rubber raw rubber is one or more of silicone rubber, fluororubber, fluoroether rubber, fluorosilicone rubber, nitrile rubber, hydrogenated nitrile rubber, polyurethane rubber, ethylene-propylene rubber, styrene-butadiene rubber, natural rubber, polybutadiene rubber, isoprene rubber, acrylate rubber and the like; wherein the second type of low-temperature resistant rubber preferably contains hydrogenated nitrile rubber, and the proportion of hydrogenated nitrile rubber is greater than or equal to 70%.
6. The method according to claim 1, characterized in that The mass concentration of the mixed glue solution of fluorinated polyphosphazene and the second low-temperature resistant rubber raw rubber is 10%-15%, which is beneficial to uniformly disperse the filler and also helps the volatilization of the solvent.
7. The method according to claim 1, characterized in that The filler is one or more of a reinforcing agent, an accelerator, a vulcanizing agent, etc.; the reinforcing agent is a carbon black / white carbon black mixed in a mass ratio of 3:1, the particle size of the carbon black is 60-100 nanometers, the particle size of the white carbon black is 50-100 nanometers, and the added mass fraction is 5-15 parts; The accelerator is one or a combination of zinc oxide, magnesium oxide, zinc stearate and magnesium stearate, and the added mass fraction is 6 to 10 parts; The vulcanizing agent is a peroxide vulcanizing agent or a compound of a peroxide vulcanizing agent and sulfur. The compounding mass ratio is preferably 1:
1. The peroxide includes at least one of the following: dicumyl peroxide, di(tert-butylperoxyisopropyl)benzene, dibenzoyl peroxide, di(2,4-dichlorobenzoyl)peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(peroxybenzoyl)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, di-tert-butyl peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, etc., and the added mass fraction is 0.1 to 5 parts.
8. The method according to claim 1, characterized in that The vulcanization process is 0.5 hour at 60-90°C and 2 hours at 120-160°C.
9. An elastomer prepared according to the method according to any one of claims 1 to 8.
10. Use of the elastomer prepared by the method according to any one of claims 1 to 8 as a sealing material.
Citation Information
Patent Citations
Hydrophobic oil-resistant flame-retardant anticorrosive multifunctional coating and preparation method
CN109852242A
Wide-temperature-range medium-resistant rubber composite material and preparation method thereof
CN113234325A
Fluorine-containing porous material and nano microspheres prepared from amphiphilic polyphosphazene stable fluorine-containing emulsion
CN115873170A